Comparison of multimodal attract-and-kill formulations for managing Drosophila suzukii: Behavioral and lethal effects. - Arun Babu; Elena M Rhodes; Cesar Rodriguez-Saona; Oscar E Liburd; Conor G Fair; Ashfaq A Sial (PLoS ONE, 2023)
Attract-and-kill (A&K) is a potential alternative control tactic for managing the invasive spotted-wing drosophila, Drosophila suzukii Matsumura. Here, we compared the efficacy of two novel A&K formulations based on proprietary blends-ACTTRA SWD OR1 (henceforth OR1) and ACTTRA SWD TD (henceforth TD)-in managing D. suzukii. Using two-choice bioassays, we compared OR1 and TD for their relative attractiveness to adult D. suzukii. Additionally, we tested how the addition of (1) a red dye (visual cue) and (2) the insecticide spinosad (Entrust™) to the OR1 and TD formulations influenced the attraction of adult D. suzukii in the presence of blueberry fruits. Finally, complementary laboratory efficacy (no-choice) bioassays were conducted to assess the mortality of adult D. suzukii exposed to OR1 and TD. A direct comparison between TD and OR1 formulations indicated the TD formulation was ~8 times more attractive than OR1. Adding a red dye to the TD or OR1 formulation did not significantly alter the attraction or mortality of adult D. suzukii compared to the formulation without a dye. Similarly, irrespective of dye status, adding spinosad to either the TD or OR1 formulation did not alter the adult D. suzukii behavioral response to these formulations but resulted in significantly higher D. suzukii mortality. Overall, the TD formulations resulted in significantly higher, or at least comparable, mortality to the OR1 formulations. In summary, our laboratory results demonstrated the higher efficacy of a TD-based A&K product in managing D. suzukii over its well-tested predecessor, the OR1 formulation, confirming its potential as a new behavioral tactic against this pest.